Relationships Among Extreme Sports Participation, Sensation Seeking, and Negative Risky Behaviors of Middle-School Students - Chunmei, Hu; Lingling, He; Ning, Ge; Yang, Li (Frontiers in Psychology, 2021)
Objective: The aim was to investigate the relationships among extreme sports participation, sensation seeking, and negative risky behaviors (smoking, drinking alcohol, and gambling) for middle-school students. Methods: Using a convenience sampling procedure, all students in a middle school in a district of Chongqing were selected to participate in the survey, which included questions on their extreme sports participation rate, and smoking, drinking alcohol, and gambling behavior. Results: A sample of 2,987 middle-school students participated in this study. The results showed that the proportions of students participating in extreme sports, smoking, drinking alcohol, and gambling were 19.9%, 4.8%, 18.4%, and 3.0%, respectively. There were significant differences between categories for gender, school, place of residence, smoking, drinking, gambling, and sensation seeking. Students who participated in extreme sports were male, attended junior school, came from urban areas, smoked, drank alcohol, gambled, and were classified as high-sensation-seeking students at a relatively higher rate than their counterparts. Alcohol drinking, gambling, and sensation seeking were associated with extreme sports participation, and the students who drank alcohol, gambled, and were high sensation seeking were more likely to participate in extreme sports than were members of the other categories. Conclusion: Middle schools should integrate extreme sports education into physical education and risky-behavior education, strengthen relevant knowledge and safety training, and guide students to meet their sensation-seeking needs through participation in extreme sports.